The Outcome of O-shape and Y-shape Nd:YAG Laser Capsulotomy in Patients with Posterior Capsule Opacification: Poster Presentation - Observational Study - General practitioner - Daniel Atnil; Yoseph Siahaan (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : Neodymium:yttrium-aluminium-garnet (Nd:YAG) laser capsulotomy is the method of choice in secondary cataract. Nd:YAG laser capsulotomy is a safe and effective method in treating decreased visual acuity. This study was conducted to determine the outcomes of Nd:YAG laser capsulotomy with O shape and Y shape in patients with posterior capsule opacification. Methods : This descriptive study was conducted in Siloam Karawaci General Hospital from February – March 2023. We included all patients with posterior capsule opacification who underwent Nd:YAG laser capsulotomy. The outcome included pre- and post-procedure uncorrected visual acuity (UCVA) after 1 week follow-up. Results : A total of six eyes from five patients (two men, three women) were included in this study. Three subjects underwent Nd:YAG laser with O-shape and three subjects with Y-shape. All subjects with O- shape had improved UCVA (0.7 to 1.0; 0.2 to 0.5; 0.5 to 0.8). Meanwhile, all subjects with Y-shape also had improved UCVA (0.2 to 0.5; 0.2 to 0.3; 0.5 to 0.7). No subjective symptoms reported following capsulotomy procedure in all patients. Conclusion : Nd:YAG laser posterior capsulotomy with O shape provided better UCVA than Y shape.